310Plasma exosomes from rats and humans protect the myocardium from ischemia-reperfusion injury. (15th July 2014) - Vicencio, JM; Zheng, Y; Das, D; Boi-Doku, C; Sivaraman, V; Hall, AR; Yellon, DM; Davidson, SM
Abstract: Introduction: Ischemia-reperfusion injury (IR) is a hallmark of cardiovascular disease and a major cause of death worldwide. Cardiac preconditioning is known to protect the heart from IR by activating several pro-survival transductional pathways. The fact that cardiac protection can also be achieved when preconditioning is applied to an organ remote from the heart (Remote Ischemic Preconditioning, RIPC) means that humoral factors are released from ischemic limbs into the circulation, potentially carrying a pro-survival message. Exosomes are nanometer-sized circulating vesicles, which mediate inter-cellular communication by ferrying diverse proteins and nucleic acids. Here we studied exosomes as possible mediators of RIPC. Methods: We isolated exosomes from plasma of rats or humans subjected to RIPC (3 cycles of 5 min limb-ischemia/5-min reperfusion). We characterized control (non-RIPC) or RIPC exosomes by electron microscopy, flow cytometry, western blot and nanoparticle tracking analysis. Exosomes were used in survival experiments and the signaling pathways leading to cardioprotection were studied. Results: Exosome concentration in plasma increased following RIPC in humans (from 3.5±0.3x108 to 1.1±0.3x109 exosomes/ml plasma; p<0.01, n=6), and administration of purified exosomes protected the heart from infarction in different settings including an in vivo rat model (vehicle: 48±7%; RIPC-Exosomes: 21±4%Infarct/AAR; p<0.01), ex vivo Langendorff (vehicle: 35±3%; RIPC-Exosomes: 21±3%Infarct/AAR; p<0.01), and in vitro hypoxia-reoxygenation of cardiomyocytes (43±7% reduction in cell death, p<0.01). RIPC-Exosomes triggered rapid ERK and Hsp27 phosphorylation in cultured cardiomyocytes, and the inhibition of upstream kinases MEK, or p38MAPK abolished ERK/Hsp27 phosphorylation and inhibited cardioprotection. Non-RIPC exosomes exerted similar protective properties. We propose a signaling mechanism of exosomal Hsp70, TLR4 activation, MEK/ERK/p38MAPK/Hsp27 mediating protection. Conclusions: We demonstrate that RIPC dramatically increases the concentration of exosomes in the circulation of humans and rats. Exosomes from both RIPC and non-RIPC plasma acutely activated pro-survival kinases that rapidly protected the heart against ischaemia-reperfusion injury. Exosomes may represent a novel agent with the potential to be an endogenous multi-signaling tool for cardioprotection.